Surviving the Enrollment Crisis:Challenges and Strategies of an Early Childhood Education Provider in Lampung - Nanik Yuliyanti (SEAMEO CECCEP, 2025)
This qualitative study examines how a community-based early childhood education (ECE) provider inLampung, Indonesia, namely TK Darul Ma’arif, is navigating an ongoing enrollment crisis. Against the backdropof nationwide declines in ECE participation and growing competition from free public institutions, the studyinvestigates the perspectives of four key stakeholders: the principal, a teacher, the institution committeemember, and a representative of the founding family. Using thematic analysis of semi-structured interviewsconducted in Bahasa Indonesia and translated into English, four major themes were identified: (1) perceivedcauses of enrollment decline, (2) financial and emotional impact, (3) strategies for institutional survival, and (4)resilience rooted in faith, history, and community. Findings suggest that while the school faces real financialpressures due to its reliance on tuition-based income, its ability to continue operating stems from non-materialresources such as long-standing community relationships, historical legitimacy, and a deep sense of moralresponsibility among staff and leadership. Participants also described adaptive strategies including door todoor visits around the area, shared budgeting, wide promotion regardless the limited budget, and maintainingemotional motivation through spiritual and social commitment. The study contributes to the literature on ECEsustainability by highlighting the importance of relational trust and institutional identity as well as supportivecommunity in shaping how schools survive in uncertain conditions. It calls for more inclusive and localizedapproaches in educational policy that support not only infrastructure but also the cultural and moralecosystems sustaining community-based education.